A Temporal Study on Coach Behavior Profiles: Relationships With Athletes Coping and Affects Within Sport Competition - González-García, Higinio; Martinent, Guillaume; Nicolas, Michel (Journal of Sport & Exercise Psychology, 2022)
The study aimed to identify coach behavior profiles and explore whether athletes from distinct profiles significantly differed on coping and affects experienced within 2 hr before the competition and during the competition (measuring them 2 hr after the competition). A sample of 306 French athletes (Mage= 22.24; SD= 4.91; 194 men and 112 women) participated in the study. The results revealed the emergence of two profiles: (a) a coaching engaged profile that stands out for moderate physical training and planning, technical skills, mental preparation, goal setting, competition strategies, personal rapport, and moderate negative personal rapport; and (b) a less engaged coaching profile with low physical training and planning, technical skills, mental preparation, goal setting, competition strategies, personal rapport, and moderate negative personal rapport. Memberships of coach behavior profiles were not confounded by athletes' practice experience, athlete's gender, and coach experience. Results of latent profile analyses with Bose-Chaudhuri-Hocquenghem method (BCH) method revealed that coping and affective states significantly differed across the coach behavior profiles. As a whole, the less engaged coaching profile engenders the worst outcomes in competition. In conclusion, the detection of less adaptive coaching profiles would be crucial to prevent negative outcomes in athletes during the competition. This might be using intervention programs adapted to the peculiarities of athletes from a particular coach behavior profiles.
Keywords: affective states; coaching; latent profile analysis; JCR; Scopus